Comparative study on the behaviour of the concrete sleepers / Ruzitah Supinyeh - Supinyeh, Ruzitah (1992)
For many years railway lines were always laid on tracks using wooden sleeper but the decline in timber resources as meant that timber increased in price as its value for use by other industries has been appreciated. Keretapi Tanah Melayu (K.T.M) is in the process of changing timber sleeper to concrete sleeper on lines in. East Coast of Penisula Malaysia. This is a prelimanary study in idealizing concrete sleeper within Malaysia context. It involves collecting data from the testing done by local manufacturer and comparing tha data with those overseas. Basically, the report is divided into three parts. The first part is the design : Malaysian design and some selected countries overseas. The second part is on testing, procedure and result obtained. The concluding part of the report presents some of the finding and proposal for future study is highlighted.